Knowledge and Practice Regarding Antenatal Care Among Pregnant Women Attending in a Government Hospital, Biratnagar - KC, Mamta; Rana, Muna; Shah, Bimala Kumari; KC, Nyamika; Bhattarai, Smita (Journal of Nobel Medical College, 2026)
Background: Antenatal care is one of the basic components of maternal care, on which the lives of mothers and babies depend. It is a key strategy to decrease maternal mortality in low-resource settings. The aim of the study was to assess knowledge and practice regarding antenatal care among pregnant women attending in a government hospital, Biratnagar. Materials and Methods: A descriptive cross-sectional research design was adopted to conduct this study. The study was carried out in Koshi zonal hospital, Biratnagar among 190 pregnant women attending antenatal out-patient department selected by non-probability convenient sampling technique. Data was collected by using structured interview schedule. Data were analyzed using descriptive statistics (frequency, percentage, mean and standard deviation) and inferential statistics (chi-square). Results: Finding revealed that majority (85.8%) and more than four-fifths (86.3%) of the respondents had adequate level of knowledge and practice regarding antenatal care respectively. Significant association was seen between level of knowledge and different socio-demographic variables namely place of residence (p=0.048), religion (p=0.041), educational status of women (p=0.001) and economic status (p=0.02). Also, level of practice regarding antenatal care was significantly associated with educational status of women (p<0.001) and educational status of husband (p=0.003). Conclusion: Most of the primi pregnant women had adequate level of knowledge and practice regarding antenatal care. It also showed that level of knowledge had significant association with place of residence, religious group, educational status of women, and socio-economic status. Similarly, no significant association between level of practice and selected socio demographic variables except educational status of women and husband.